2013
DOI: 10.1016/j.jad.2012.11.040
|View full text |Cite
|
Sign up to set email alerts
|

Implications of apathy and depression for everyday functioning in HIV/AIDS in Brazil

Abstract: Background Brazil accounts for the largest number of HIV+ persons in Latin America, and this epidemic poses a significant public health burden in this country. Little is known about the neuropsychiatric and functional consequences of HIV infection in this population. Methods Participants were 43 HIV+ and 29 HIV- individuals who underwent a neuropsychological, psychiatric and neurological evaluation that included self-report measures of mood (Beck Depression Inventory-II; BDI-II), neurocognitive complaints (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 46 publications
2
29
1
2
Order By: Relevance
“…Raw scores were converted into age and education corrected T scores. T scores greater than 65 were considered clinically elevated, which is consistent with previous literature [13, 22, 34]. In the present sample, 36.6 percent met criteria for clinically significant apathy.…”
Section: Methodssupporting
confidence: 91%
See 2 more Smart Citations
“…Raw scores were converted into age and education corrected T scores. T scores greater than 65 were considered clinically elevated, which is consistent with previous literature [13, 22, 34]. In the present sample, 36.6 percent met criteria for clinically significant apathy.…”
Section: Methodssupporting
confidence: 91%
“…Additionally, both conditions frequently co-occur in PLWH [1113]. Furthermore, depression has been associated with reduced adherence to Antiretroviral (ARV) medication [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Poor functional ability may also be attributed to pain discomfort, which is a symptom of an illness. Albeit there is preponderance of literature indicating depression negatively affects functional ability (Kamat et al, 2013;Scuteri et al, 2011;Lee et al, 2006;Penninx, Deeg, van Eijk, Beekman, & Guralnik;Stuck et al, 1999), results of our study showed that functional ability negatively affects depression. This finding is similar to Vink, Aartsen, and Schoevers's (2008) study indicating that functional limitations is a predictor of depression.…”
Section: Age Functional Ability Number Of Chronic Illnesses and Decontrasting
confidence: 49%
“…(4) In PLHA, it is known for being negatively associated with worse compliance with antiretroviral treatment, (5) therapeutic outcomes and risk behaviors, (6) besides its considerable impact in the treatment and social relationships (7) and in the more rapid progression to Aids and death. (1) Hence, the importance of measuring and understanding the influence of depression in this population is highlighted.…”
Section: Introductionmentioning
confidence: 99%